25 Jahre : galerie Fahnemann Berlin. - Galerie Fahnemann, Berlin (Belin : Galerie Fahnemann Berlin, 2005)
Hartung, Hans ; Girke, Raimund ; Förg, Gunther ; Knoebel, Imi ; Klein, Astrid ; McLean, Bruce ; McCollum, Allan ; Kusama Yayoi ; Nannucci, Maurizio ; Pitz, Hermann ; Metzel, Olaf ; Virnich, Thomas ; Wesely, Michael ; Scholz, Frances ; Mangold, Julia ; Trixl, Daniela ; Zitzwitz, Thomas ; Kaeseberg ; Judd, Donald ; LeWitt, Sol ; Stella, Frank ; Mangold, Robert ; Bourgeois, Louise ; Pettibon, Raymond
Exhibition "25 Jahre" in Galerie Fahnemann, Berlin, 01.10.2005 - 20.12.2005
Duits en Engels
Engels
boek